2018
DOI: 10.1002/cmdc.201800632
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Protein Kinase CK1δ with Riluzole: Could It Be One of the Possible Missing Bricks to Interpret Its Effect in the Treatment of ALS from a Molecular Point of View?

Abstract: Riluzole, approved by the US Food and Drug Administration (FDA) in 1995, is the most widespread oral treatment for the fatal neurodegenerative disorder amyotrophic lateral sclerosis (ALS). The drug, whose mechanism of action is still obscure, mitigates progression of the illness, but unfortunately with only limited improvements. Herein we report the first demonstration, using a combination of computational and in vitro studies, that riluzole is an ATP‐competitive inhibitor of the protein kinase CK1 isoform δ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…This event reduces the ability of SQSTM1 to eliminate the polyubiquitinated proteins by autophagy clearance creating a toxic micro-environment for the neurons and thus cell death (Lee et al, 2019). (Battaini, 2001). Regarding their implications in ALS, it was described that PKC activity was increased in ALS patients, suggesting that alterations in this kinase have effects on neuronal viability through the regulation of voltage-dependent Ca 2+ channels (Krieger, Lanius, Pelech, & Shaw, 1996).…”
Section: Protein Tyrosine Kinase 2 (Ptk2) Inhibitorsmentioning
confidence: 99%
“…This event reduces the ability of SQSTM1 to eliminate the polyubiquitinated proteins by autophagy clearance creating a toxic micro-environment for the neurons and thus cell death (Lee et al, 2019). (Battaini, 2001). Regarding their implications in ALS, it was described that PKC activity was increased in ALS patients, suggesting that alterations in this kinase have effects on neuronal viability through the regulation of voltage-dependent Ca 2+ channels (Krieger, Lanius, Pelech, & Shaw, 1996).…”
Section: Protein Tyrosine Kinase 2 (Ptk2) Inhibitorsmentioning
confidence: 99%
“…On the other hand, CK1δ has emerged as a potential target for other diseases. CK1δ inhibitors have been proposed to inhibit the phosphorylation of TDP-43, a pathological hallmark of central nervous system (CNS) diseases, such as amyotrophic lateral sclerosis (ALS) and frontotemporal dementia [33,34]. CK1δ is also a potential target for Parkinson's disease and pulmonary fibrosis [35,36].…”
Section: Aging Discussionmentioning
confidence: 99%
“…Recent studies have suggested that riluzole may exert its actions through a direct link on TDP-43 self-interaction, without change to total TDP-43 levels in neuroblastoma cells in vitro (30). Furthermore, it has been hypothesised that expression of a truncated protein kinase, CK1δ, leads to phosphorylation, mislocalisation and aggregation of TDP-43 (31), and that riluzole is may inhibit this process (10). However, in contrast to these results, we observed no alteration of TDP-43 phosphorylation nor decreases to insoluble TDP-43 with riluzole treatment, indicating that riluzole may not exert these effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, people with ALS have increased levels of the excitatory neurotransmitter glutamate in cerebrospinal fluid (CSF) (6), and altered excitability of motor neurons may be an early feature of disease (7,8). Amongst a myriad of other potential disease-relevant effects of riluzole, the drug has also been proposed to affect estradiol transport (9), to inhibit kinases potentially involved in ALS pathology (10), and to decrease activation of the heat shock response related to protein aggregation (11).…”
Section: Introductionmentioning
confidence: 99%